Caracterização química de extratos de plantas medicinais por LC-MS/MS e resposta in vivo da atividade anticonvulsivante da Jatropha gossypiifolia L. - Gobo, Luciana Assis (2017)
In this paper, two methods using LC-MS/MS were developed for the chemical characterization of Amazonian medicinal plants and evaluated the anticonvulsive response in vivo. An analytical method using LC-APPI-MS/MS with toluene as a dopant was developed for the determination of 12 triterpenes that demonstrated biological activity in extracts of medicinal plants. The limits of detection and quantification ranged from 0.4 to 157.9 μg L-1 and 1.3 to 526.4 μg L-1, respectively. The method was validated and applied to extracts of 7 species of medicinal plants (Mansoa alliacea, Bauhinia variegata var variegata, Bauhinia variegata var alboflava, Cecropia obtuse Trécul, Cecropia palmate Willd, Connarus perrotettii var angustifolius e Jatropha gossypiifolia L.) from the Amazon region. Ten triterpenic compounds were determined (arjunic acid, betulinic acid, ursolic acid, maslinic acid, α-amirin, β-amirin, erythrodiol, friedelin, lupeol and sitosterol) in all species studied in hydroethanolic extracts, acetate fraction and butanolic fraction. The species with the highest number of triterpenic compounds were Bauhinia variegata and Cecropia obtuse, and the species with the highest concentration of compounds was Jatropha gossypiifolia. Triterpenic markers were: α-amirin, β-amirin, lupeol, sitosterol and ursolic acid. A second analytical method was developed for the determination of prostaglandins (PGs) using LC-ESI-MS/MS. The following compounds were identified: thromboxane B2, prostaglandin E2, prostaglandin D2, 6-keto-prostaglandin F1 alpha and prostaglandin F2 alpha. The limits of detection ranged from 0.25 to 1.09μg L-1, and the limits of quantification ranged from 0.83 to 3.64μg L-1. The method was validated and applied to samples of brain tissue. Since the species Jatropha gossypiifolia presented higher concentration of terpene compounds, its anticonvulsant activity was evaluated. Male Swiss mice (25 to 30 g) were used. Animals were kindled by intraperitoneal injection with PTZ three times a week for 5 weeks. The animals that have reached the kindling criterion and non-kindling animals were then treated with hydroethanolic extract of Jatropha gossypiifolia. The neuroprotective capacity of the hydroethanolic extract of Jatropha gossypiifolia at a dose of 10mg kg-1 was observed in kindling and non-kindling mice, as it increased the latency for generalized seizures (F=4.97 e P=0.033). With the determination of prostaglandins levels brain tissues it is possible to infer that the action of the hydroethanolic extract of Jatropha gossypiifolia, reduces the levels of prostaglandins and is able to reverse the acute PTZ effect. The extract itself increases basal level of prostaglandins and this may occur due to snitrosylation/ activation of COX-2, that initiates the generation of prostaglandins. It can also be assumed that the extract potentiates the action of the enzyme isomerase towards the formation of PGD2, since this prostaglandin has an anticonvulsive activity against seizures triggered by PTZ.